MAINTAIN OF AFRICAN CATFISH (Clarias gariepinus) USED OF PEAT SWAMP WATER IN BIOFLOCS TECHNOLOGY - Taharudin, M; Tang, Usman M; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from December 2015 until January 2016 at Technology Research and Development Center in Riau Balitbang. The purpose of this research was to investigate growth and survival rate of african catfish with difference of stocking density in bioflocs techniques. This research using experimental method and completely random design (RAL) with three treatment and three replications, three are P1 : Stocking density 200 ekor/m3, P2 : Stocking density 300 ekor/m3, P3 : Stocking density 400 ekor/m3. The result showed that african catfish with difference of stocking density in bioflocs techniques significant effect on quality of water, absolute length growth, spesific growth rate, the growth of absolute weight, and survival rate. The best treatment were obtained in treatment stocking density 300 ekor/m3, with value growth of quality of water (temperature 27-32oC, DO 3,09-4,16 mg/L, pH 6,7-7,1 and NH3 0,07-0,09 mg/L) absolute weight 50,15 g, growth in absolute length 12,63 cm, specific growth rate 3,99% and survival rate 98,16%.Keyword : african catfish, stocking density, Bioflocs technology